Assessment of Anticancer Effect of Alendronate in Breast Cancer: An In vitro Study - Syed Amber Ilyas, Nida; Zarina, Shamshad; Hashim, Zehra (Journal of Biotechnology and Biomedical Science, 2019)
Breast cancer has high incidence in women from both developed and developing countries. Approximately 2 million women are diagnosed with breast cancer in 2018. In Asia, unfortunately Pakistan leads the highest number of breast cancer patients. Various treatment strategies are present but they are not well developed. There is a great need to develop effective methods for early detection and treatment of the disease. For cancer treatment chemotherapeutic interventions have always been a method of choice. One of the mechanisms involved in cancerous cell proliferation is Mevalonate (MVA) pathway. It is hypothesized that arresting MVA pathway leads to cell death hence cancer cell growth is suppressed. Various inhibitors of MVA pathway have been studied that can suppress cell proliferation. Nitrogen containing bisphosphonates are MVA pathway inhibitor and clinically used for treatment of bone diseases. Their anticancer efficacy is also reported. Current study focuses on alendronate, a nitrogen containing bisphosphonate to examine their anticancer effect on breast cancer cell line. Results of this study may help in addition of new anticancer drug for breast cancer.
Keywords: Bisphosphonates; Alendronate; MVA Pathway; Anticancer; Breast cancer